ASPECTS OF COPRA PRODUCTION AND MARKETING IN VANUATU - Martin R Fowler (International Coconut Community Journal, 1987)
Coconuts occupy the largest area under any crop in Vanuatu and provide employment and incomes for the majority of the rural population; copra exports have provided far and away the most important source of foreign exchange earnings during most of the past one hundred years, and their position remains paramount. Copra exports also provide an important source of Government revenue; and. finally, coconuts are an important component of the national diet. Given the fundamental importance of the coconut subsector to the economic life of the country, a deeper understanding of its recent and projected evolution is essential for macro‑economic policy formulation.